Unraveling Hemodynamic Complex in White Matter Hyperintensities - Weidong Zhou (Journal of Alternative, Complementary & Integrative Medicine, 2026)
As both a neurologist and a co-author of the recently article, I appreciate the opportunity to provide a professional commentary that extends beyond the published discussion, situating our findings within the latest advances in Cerebral Small Vessel Disease (CSVD) research